2009
DOI: 10.1002/we.336
|View full text |Cite
|
Sign up to set email alerts
|

Active control of flow separation and structural vibrations of wind turbine blades

Abstract: The feasibility of using synthetic jet actuators to enhance the performance of wind turbine blades was explored in wind tunnel experiments on a small scale model blade. Using this technique, the global fl ow fi eld over the blade was altered such that fl ow separation was mitigated. Consequently, this resulted in a signifi cant decrease in the vibration of the blade. Global fl ow measurements were conducted, where the moments and forces on the blade were measured using a six component wall-mounted load cell. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 32 publications
0
29
0
Order By: Relevance
“…According to Maldonado et al [14], the strength of the synthetic jets (relative to the momentum of the external flow) is quantified using the momentum coefficient, C µ , defined as the following:…”
Section: Active Flow Control Techniquementioning
confidence: 99%
See 3 more Smart Citations
“…According to Maldonado et al [14], the strength of the synthetic jets (relative to the momentum of the external flow) is quantified using the momentum coefficient, C µ , defined as the following:…”
Section: Active Flow Control Techniquementioning
confidence: 99%
“…Separation control using synthetic jets has recently been demonstrated as a viable means to reduce wind turbine blade structural vibration, Maldonado et al [14] by exploiting the narrow-band receptivity of the separating shear layer and the upstream boundary layer to external actuation. Previously, Oster and Wygnanski [15] and Roberts [16] showed that V. Maldonado, S. Gupta the actuation can affect the global flow field by modifying the evolution and interactions of the large-scale vortical structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Use of active strut elements based on resonant controllers [15] inspired by the concept of TMDs has been proposed for active control of vibrations in wind turbines. Investigations on the use of synthetic jet actuators [16], microtabs and trailing edge flaps [17,18] have also been considered by researchers. Active control strategies have been proposed by Staino et al [19] and Fitzgerald et al [14].…”
Section: Introductionmentioning
confidence: 99%